1985
DOI: 10.3168/jds.s0022-0302(85)81032-8
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Response to Growth Hormone-Releasing Factor in Selected and Control Holstein Heifer Calves

Abstract: Holstein heifer calves from selected and control lines were treated with growth hormone-releasing factor to determine whether the magnitude of the pituitary growth hormone response is associated with genetic potential for milk yield. Cows in the selected line were bred to highest Predicted Difference milk sires available each year, while control line cows were bred to bulls that were average for 1964 milk production. Eight calves from each line of similar age (206 to 210 days) and weight (205 kg average) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
2
4
0
Order By: Relevance
“…The results of this study could not confirm the positive associations between GH release and breeding value for milk yield established in other dairy cattle selection experiments (Zinn et al, 1994;Woolliams et al, 1993;Løvendahl et al, 1991). However, the results are in agreement with the lack of association found in calves from the selection lines used by Massri et al (1985) and later by Baumgard et al (2002).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of this study could not confirm the positive associations between GH release and breeding value for milk yield established in other dairy cattle selection experiments (Zinn et al, 1994;Woolliams et al, 1993;Løvendahl et al, 1991). However, the results are in agreement with the lack of association found in calves from the selection lines used by Massri et al (1985) and later by Baumgard et al (2002).…”
Section: Discussionsupporting
confidence: 90%
“…This suggests that the levels of GH release following artificial stimulation could be used as a selection criterion for milk yield in dairy cattle. However, in other studies GH release was not consistently related to milk yield (Massri et al, 1985;Baumgard et al, 2002). Because random genetic drift can occur within selection lines, especially if these are of limited size, the results need to be validated, preferably in unrelated cattle populations.…”
Section: Introductionmentioning
confidence: 91%
“…Thus previous work is in good agreement with our finding of a weak positive relationship. Such a result might also be expected from the effects of injecting GH releasing factor into lactating cows (M assri et al 1985). One interesting result was of a significantly negative correlation between BVs and frequency of peaks in plasma GH concentration (K lindt 1988).…”
Section: Resultsmentioning
confidence: 84%
“…Previous studies with these two genetic lines have reported conflicting results regarding the effect of selection for milk yield on circulating GH concentrations. A trend was detected for SL heifers to have greater prechallenge concentrations of GH than CL heifers at 208 ± 2 d of age (Massri et al, 1985), but these results were influenced greatly by one SL heifer. An evaluation of samples from bull calves (12/line) collected every 30 min over a 2.5 h interval determined that GH concentrations were greater in SL calves during the first 9 mo of age whether the calves were fed or deprived of feed and water for 24 h (Parchuri et al, 1993).…”
Section: Prec Gh Concentrationsmentioning
confidence: 81%
“…As summarized by Woolliams and Lovendahl (1991), considerable variation in technique, physiological stage of the animals used, and study design contribute to the variation observed among published studies designed to identify effects of selection on GH and GH response to GRF. Differences in the number of animals evaluated, the number and frequency of samples obtained prior to GRF administration, and study designs contribute to the discrepancies observed among the GRF challenge studies (Massri et al, 1985;Parchuri et al, 1993;Weber et al, 1997; this study) conducted with calves from these two genetic lines. Because the typical sampling regimen before GRF administration only captures a small portion (< 30 min) of the episodic nature of GH release, it is possible that a true representation of basal GH concentration is not obtained by this method.…”
Section: Prec Gh Concentrationsmentioning
confidence: 99%